1673a Entire populations of five countries as an occupational study cohort – does it work?. (24th April 2018) - Pukkala, E
Abstract : The Nordic Occupational Cancer (NOCCA) project was the largest and in many aspects, also qualitatively, the most unique research study ever done on occupation and cancer incidence. It consisted of a follow-up study on the entire working populations of Denmark, Island, Finland, Norway and Sweden with three million cancer cases diagnosed 1961–2005. It described risks of 84 cancer types in 54 occupational categories (astra.cancer.fi/NOCCA) and developed a Nordic Job Exposure Matrix (NOCCA-JEM) that converts the individual job histories of all Nordic people to quantitative estimates of exposure to potentially cancer-related factors. Many of the results on dose-response associations between exposures and cancers have been novel findings or have confirmed (or not) findings from earlier smaller studies. The NOCCA network still produces about one new publication each month from the old data. Still, not only the NOCCA researcher team but also institutions such as Nordic Minister Council and occupational health professionals have stressed that it would be important to continue NOCCA research work with updated data. New features in the work life, such as effects of sedentary work, could not be fully studied in the original NOCCA data. There is also an urgent need to follow effects of work safety regulations and operations that were started after the harmful effect of work carcinogens were recognised. For example, restaurant workers who had the highest risk of many cancers are no longer exposed to tobacco smoke in their work environment; this should be seen as a rapid decrease in their cancer risk. It has been proven that combining five entire national populations as a study cohort about 10 years ago was feasible and produced important results. The researchers of the NOCCA network are eager to continue and update the activity, provided that challenges related to funding and data access issues can be won.